Peak match sprinting speed during soccer matches: analysing the pre- and post-peak speed dynamics - Silva, Hugo; Nakamura, Fábio Yuzo; Racil, Ghazi; Gómez-Diaz, Antonio; Menezes, Pedro; Chamari, Karim; Marcelino, Rui (Biology of Sport, 2025)
This study aimed to characterize match peak speeds, during a 20-second time window (10 seconds immediately before and after the match peak speed), in soccer matches. Twenty elite soccer players were monitored with global navigation satellite system (GNSS) devices during six soccer matches from the Brazilian first division. After identifying the peak speed, individual speeds within 10 seconds before and 10 seconds after were collected at each 0.1 second interval (10 Hz). Intra-individual speed differences were assessed at every second of the selected window using paired mean differences (with effect sizes and 95% confidence intervals). Match peak speeds ranged from 29.11 km/h to 31.64 km/h. Speeds registered 10 seconds before and 10 seconds after the match peak speed ranged from 5.11 km/h to 9.21 km/h and 6.90 km/h to 7.65 km/h, respectively. Speed increased moderately (effect size [95% confidence interval]: 0.68 [0.64, 0.73]) 4 seconds before the match peak speed and decreased moderately (effect size [95% confidence interval]: -0.73 [-0.78, -0.68]) 3 seconds after the maximal effort. Match peak speeds were achieved from flying starts, differing from the current sprint test procedures. Players needed to accelerate from speeds of approximately 10 km/h to reach their peak speed. After the match peak speed, players decelerated faster than they accelerated but without reaching a complete stop. Nevertheless, preparing players for intense decelerations should not be disregard. Players can benefit from field tests and training sessions that provide similarities to what occurs during competition, and accelerations should also be considered when referring to peak speeds.